PSYCHOPATHIC BY THE MAIN CHARACTER OF THE MOVIE MANIAC - Mutmainnah, Mutmainnah (Journal of Innovation Research and Knowledge, 2025)
This study analyzes the representation of psychopathy in the movie Maniac, focusing on the psychopathic characteristics of Frank as the main character and the factors contributing to his behavior. A descriptive qualitative method is employed to analyze the data. Hare’s theory of psychopathy is used to identify the characteristics, while Freud’s psychoanalytic theory is applied to examine the contributing factors. The findings reveal that Frank exhibits five psychopathic characteristics: glibness and superficial charm, lack of remorse, impulsivity, poor behavioral control, and lack of empathy. Furthermore, the results indicate that Frank’s psychopathic behavior is influenced by the dominance of the id over the ego and superego